Pizarra inteligente para el aprendizaje en aulas unidocentes de la ciudad de Pampas de la región Huancavelica - Iquiapaza Machaca, Abigail Silvia (2022)
In this article, the authors implemented a prototype of a user-friendly, didactic and innovative smart whiteboard simulator, which allows optimizing the learning of the basic operations of mathematics in students from initial level to the first grade of elementary school. educational institutions of multigrade type (single teachers) of the province of Tayacaja of the Huancavelica region. For the development of the smart board prototype, the Arduino board and LEDs were used; Furthermore, a friendly interface has been developed in the mBlock software; where basic math operations are presented. The methodology used in the development of the prototype is based on 4 phases: understanding the problem, plan of activities, execution of activities and testing or evaluation of the solution. This work was developed in the Information Management course with students of the II cycle of the industrial engineering career.